Towards Sustainable and Coordinated Methods for Estimating Open Access Costs at Canadian Higher Education Institutions - Hare, Madelaine; Butler, Leigh-Ann; Savage, Stephanie (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
Higher education institutions in Canada aim to provide access to knowledge through subscriptions and investments in OA publishing. As subscription and OA publication costs continue to increase, some institutions have established funds to support authors’ payment of publication fees. Others have adopted models such as read-and-publish deals or “transformative agreements”, where institutions pay publishers a lump sum for subscriptions and publishing fees for authors. As institutions continue to subscribe to journals, support authors with OA publishing, and negotiate agreements, accurately estimating institutional OA spending is imperative to determining the cost effectiveness of deals and necessary funding support for authors. Methods to estimate OA costs have largely developed in silos across the country. This commentary presents observations derived from work performed across Canada on the challenges accompanying OA estimation and calls for a more coordinated approach to establish standardized, sustainable methods. Calibrating efforts across institutions can support the development of reliable methodologies and streamline resources helpful for the more efficient performance of the often onerous task of estimating costs.